Relationship Between Inflammatory Infiltrate Canine Mammary Carcinomas. - Mayara Caroline ROSOLEM; Filipe Santos FERNANDO; Pamela Rodrigues Reina MOREIRA; Rosemeri de Oliveira VASCONCELOS (Journal of Veterinary Healthcare, 2017)
The mammary tumor is one of the most common cancer in female dogs and, at the present days, there is a big focus on the study of the relation between this kind of tumor in animals and the cells that stay around them, like the inflammatory cells. The objective of this study was to evaluate and show where the inflammatory cells stay in simple mammary carcinomas in female dogs by immunohistochemistry. Samples of simple mammary carcinomas (tumor group; n=26) and mammary gland samples without tumor (control group; n=18) were submitted to immunohistochemical analysis for the detection of T lymphocytes, macrophages, plasma cells and the MHC-II molecule. The mast cells were evaluated by the histochemical technique (toluidine blue). Lymphocytes, macrophages and mast cells were observed distributed in the tumor stroma. MHC-II was detected in tumor cells and in the inflammatory infiltrate. Plasma cells predominated in the peritumoral stroma. Macrophages differed significantly between the two groups and predominated in the tumor group. In the comparison between histological types of mammary carcinomas, mast cells differed significantly between solid tumors of the tubular / papillary types. The cytoplasmic immunodetection of MHC-II was suggested an inefficient antigen presentation. Some of the leukocytes present in the tumor infiltrate, appear to be exerting a pro-tumor effect and allowing the progression of tubular and papillary carcinomas. But in solid carcinomas (may be poorly immunogenic), as they had the lowest proportion of leukocytes present in the tumor site. More studies are necessary to confirm these results, such as the determination of the cytokine profile and the predominant leukocyte subpopulations in the tumor microenvironment.
Keywords: breast neoplasia